Patella radiograph image texture: The correlation with lumbar spine bone mineral density values - Mulyono, Agus; Islam, Md. Monirul; Panse, Vishal R (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
Osteoporosis is a common metabolic disease that is frequently overlooked. This disease primarily affects adult women and causes bone thinness and fragility, which leads to fractures. DXA (Dual Energy X-ray Absorptiometry) is used to diagnose osteoporosis by measuring bone mineral density. These devices are expensive and not widely available for treatment. This study aimed to find a correlation between the texture value of an image of the patellar bone and the density of the lumbar spine, which can then be used to detect osteoporosis. This study's sample size was 19 subjects, and their bone mineral density (BMD) was measured using DXA. An X-ray was then taken to obtain an image of the genu bone. The stages of the research are as follows: 1) preparing the X-ray image of the bone; 2) determining the image texture value method of gray level co-occurrence matrix 3) investigating the relationship between texture values and BMD in the lumbar spine. The correlation test results revealed a statistically significant correlation between the texture value and the BMD of the lumbar spine for the correlation and variance characteristics (P less than 0.05). As a result, the value of the texture of the image of the patella bone can be used to detect osteoporosis.